SAT0280 Efficacy of Apremilast, An Oral Phosphodiesterase 4 Inhibitor, on Physical Function and Pain in Patients with Psoriatic Arthritis, Including Current Skin Involvement: Results of a Phase 3, Randomized, Controlled Trial. (23rd January 2014) - Birbara, C.; Blanco, F. J.; Crowley, J. J.; Hu, C.; Stevens, R.; Edwards, C. J.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to modulate inflammatory mediators. Objectives: PALACE 3 compared APR vs placebo (PBO) in patients with active psoriatic arthritis (PsA) and 1 or more ≥2-cm psoriatic lesion at baseline (BL) despite prior DMARDs and/or biologics. Methods: Patients were randomized 1:1:1 to PBO, APR 20 mg BID, or APR 30 mg BID stratified by BL DMARD use. At wk 16, patients with <20% reduction in both swollen and tender joint counts were required to be re-randomized to APR 20 mg BID or 30 mg BID (early escape) if first randomized to PBO or remained on initial APR dose. Patients continued treatment through wk 24. Stable concurrent DMARD therapy was allowed (MTX, sulfasalazine, leflunomide, or combination). Efficacy analyses were conducted using the per-protocol population (N=476). Missing data were handled using NRI for categorical endpoints and LOCF for continuous endpoints. Results: 505 patients were randomized, including 27.9% with prior biologic exposure and 8.7% considered biologic failures. At BL, 60.6% were taking DMARDs, of which 85.7% were taking MTX (mean dose, 14.75 mg/wk). At wk 16, significantly more patients receiving APR 20 mg BID (29.4%; P =.02) and 30 mg BID (42.8%; P <.0001) achieved the primary endpoint of an ACR20 vs PBO (18.9%). At wk 24, significant improvements across multiple secondary endpoints were seen with APR vs PBO, including physical function, fatigue and pain (Table ). There was a dose-related effect observed with greater efficacy generally seen in patients receiving APR 30 mg BID. A significantly greater proportion of patients receiving APR 30 mg BID achieved minimal clinically important differences for HAQ-DI and achieved a good or moderate EULAR response or PsARC response vs PBO. APR was generally well tolerated. The most common AEs were diarrhea, nausea, headache, and URTI. Of patients with AEs, the majority (>93%) were mild or moderate; discontinuation rates due to AEs were low (6-8%). Conclusions: APR significantly improved signs and symptoms of PsA and resulted in statistically and clinically meaningful improvements in physical function and pain. References: Kwok T, Pope JE. J Rheumatol 2010;37:1024-8. Mease PJ, Woolley JM, Bitman B, Wang BC, Globe DR, Singh A. J Rheumatol 2011;38:2461-5. Disclosure of Interest: C. Birbara Grant/research support from: Amgen, Lilly, Pfizer, Incyte, Merck, Bristol-Myers Squibb, F. Blanco Consultant for: Pfizer, Bioiberica, Gebro Farma, J. Crowley Grant/research support from: Abbgvie, Amgen, Celgene, Janssen, Merck, Pfizer, Consultant for: Abbvie, Amgen, Speakers bureau: Abbvie, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support from: Pfizer, Consultant for: Samsung, Roche, Celgene, Speakers bureau: Roche, Pfizer, Abbott, GSK